Marbury v. Madison and R (Miller) v. the Prime Minister An Attempt at Comparative Constitutional Rhetoric (Philippine Law Journal, 2021)
Marbury v. Madison is regarded as one of the most seminal court opinions of modem times. Its enduring legacy is rooted in its constitutional rhetoric, which this Article defines as the operationalization of rhetorical techniques and methodologies for constitutional discourse in court decisions. In the United Kingdom (U.K.), the equivalent of Marbury seems to be R (Miller) v. The Prime Minister, which concerned the propagation of the U.K. Parliament in 2019 leading up to the next parliamentary elections and in anticipation of the U.K's exit from the European Union (EU). The constitutional rhetoric of both Marbury and Miller highlights the importance of the persuasive character of judicial opinions meant for their greater audiences. The "how" of constitutional rhetoric concerns the multiple options available to judges that collectively constitute either “cloaking devices”, “deflector shields”, or a reasoning. The composition of Marbury's constitutional rhetoric is genius, with its easily identifiable and logical flow, carving up of the issues, and intentional contrasts and long deductions with a peppering of legal distinctions and delineations, among others. Miller has its own distinct and logical flow as well, along with other similarities, but it also has its own bolder, more relevant, more impactful, and more assertive signature of constitutional rhetoric because of its modem context. In the end, it is perhaps unwise to compare Marbury and Miller because of their differing contexts, but constitutional scholarship is all the better for it.